Determinan Perilaku, Etika, dan Finansial terhadap Penggunaan Buy Now, Pay Later (BNPL): Tinjauan Literatur Sistematis - Bayu Liano Leader Habibullah; Mudjahidin (Jurnal Algoritma, 2026)
This study presents a Systematic Literature Review (SLR) of 30 peer-reviewed articles on the adoption, behavioral dynamics, and financial implications of Buy Now, Pay Later (BNPL) services. Using the SPAR-4-SLR protocol and the TCCM framework, this review integrates findings from fintech, consumer behavior, behavioral economics, and digital credit research. The results show that BNPL studies primarily employ behavioral and technology acceptance theories, such as TAM, TPB, UTAUT, and impulsive buying theory. Research is largely concentrated in Indonesia, Malaysia, Australia, the United States, and the United Kingdom. The main factors influencing BNPL usage intention include perceived usefulness, trust, affordability, convenience, impulsive tendency, and financial literacy. Most studies use quantitative survey-based methods, while qualitative approaches, mixed methods, and secondary data remain limited. This review identifies gaps in theory, context, methodology, and constructs, while also opening opportunities for future research, such as multi-theory integration, cross-country comparisons, and studies on financially vulnerable groups. Practical implications for policymakers and BNPL service providers include improving transparency, promoting responsible lending practices, and strengthening consumer protection. Research limitations, such as the focus on B2C BNPL, the exclusion of B2B models, and reliance on secondary data, provide opportunities for further empirical research.